Calcaneal Tendon Regions Exhibit Different MMP-2 Activation After Vertical Jumping and Treadmill Running - de Mello Malheiro, Olga Cristina [UNESP]; Giacomini, Camila Tateishi [UNESP]; Justulin, Luis Antonio [UNESP]; Delella, Flávia Karina [UNESP]; Dal-Pai-Silva, Maeli [UNESP]; Felisbino, Sergio Luis [UNESP] (Wiley-liss, 2009)
Increased activity of matrix metalloproteinases (MMPs) -2 and -9 was found in calcaneal tendon after physical training. However, little attention has been given to the distinct biomechanical and tissue structure of the calcaneal tendon's proximal and distal regions. Herein, we evaluated the effect of two types of physical activities on tendon morphology and matrix metalloproteinase activities in the proximal and distal regions of rat calcaneal tendon, separately. Adult male Wistar rats from control, water-adapted, vertical-jumping, and treadmill-running groups were sacrificed after 1 or 4 days of physical exercise, 6 hr after the end of that day's exercise session. Tendons were processed for histology, morphometry, and gelatin zymography. Tendons from adapted and trained animals showed active secretory cells and increased thickness, cellularity, and blood vessel volume fraction of peritendinous sheath, but without inflammatory process. In the proximal region, both pro- and active MMP-2 were increased after vertical jumping, but only pro-MMP-2 was increased after treadmill running. In contrast, in the distal region, both exercise types increased the activity of pro- and active MMP-2, especially treadmill running, which increased the active MMP-2 by about 11- and eightfold, respectively, after 1 and 4 days of training. No activity of MMP-9 was observed in either tendon region in this study. In conclusion, distal and proximal regions of calcaneal tendon exhibit differential intensities of tissue remodeling after treadmill running or vertical jumping and MMP-2, in the absence of inflammation, plays a major role in this adaptive response. Anat Rec, 292:1656-1662, 2009. (C) 2009 Wiley-Liss, Inc.
Keywords: tendon; matrix metalloproteinases; physical training; exercise; compressive loading; zymography